Blood microbiome signatures in systemic diseases: current insights, methodological pitfalls, and future horizons - Khan, Ikram; Irfan, Muhammad; Khan, Imran; Noor, Uzma; Xie, Xiaodong; Li, Zhiqiang (Frontiers in Cellular and Infection Microbiology, 2025)
The human-associated microbiome, encompassing diverse microbial communities across body sites, plays a pivotal role in maintaining host homeostasis. Disruption of this balance, termed dysbiosis, has been implicated in a spectrum of pathophysiological conditions. Traditionally, blood was considered a sterile microenvironment. However, emerging insights into the blood microbiome challenge the paradigm of blood sterility, revealing microbial signatures, including cell-free DNA and viable taxa, with putative implications for host physiology and disease. The blood taxonomic profile at the phylum level is dominated by Proteobacteria, with Bacteroidetes, Actinobacteria, and Firmicutes following in abundance. Dysbiosis in blood microbiome composition may indicate or contribute to systemic dysregulation, pointing to its potential role in disease etiology. These findings highlight the blood microbiome as a possible driver in the pathogenesis of infectious and non-infectious diseases, neurodegenerative disorders, and immune-mediated conditions. The detection of specific microbial profiles in circulation holds promise for biomarker discovery, enhancing disease stratification, and informing precision therapeutic strategies. However, advancing this field requires overcoming methodological challenges, including contamination control, standardization, and reproducibility. This review aims to present blood microbiome biomarkers across infectious, non-infectious, neurodegenerative, and immune-mediated diseases, while critically examining methodological variations, controversies, limitations, and future research directions. Elucidating these factors is critical to advancing blood microbiome biomarker validation and therapeutic targeting, thereby refining mechanistic insights into systemic disease pathogenesis.